2022
DOI: 10.3390/jcdd9050140
|View full text |Cite
|
Sign up to set email alerts
|

Association of Catheter Ablation and Reduced Incidence of Dementia among Patients with Atrial Fibrillation during Long-Term Follow-Up: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Atrial fibrillation (AF) is independently associated with the onset of cognitive decline/dementia. AF catheter ablation (AFCA) is the most effective treatment strategy in terms of sinus rhythm maintenance, but its effects on dementia prevention remain under investigation. The aim of the present study was to perform a systematic review and meta-analysis of the presently available studies exploring the effect of AFCA on dementia occurrence. Methods: PubMed/MEDLINE databases were screened for articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
0
5
0
1
Order By: Relevance
“…Two previous meta-analyses also examined the relationship between AF ablation and dementia. A meta-analysis of 4 studies by Saglietto et al ( 48 ) showed that AF ablation is associated with a nearly 50% reduction in dementia occurrence. Another meta-analysis by Bodagh et al ( 49 ) found that AF ablation was associated with a lower risk of subsequent dementia diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous meta-analyses also examined the relationship between AF ablation and dementia. A meta-analysis of 4 studies by Saglietto et al ( 48 ) showed that AF ablation is associated with a nearly 50% reduction in dementia occurrence. Another meta-analysis by Bodagh et al ( 49 ) found that AF ablation was associated with a lower risk of subsequent dementia diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was associated with greater arrhythmia-free survival (RR 0.62, 95% CI 0.51–0.74, p < 0.001) and less hospitalizations (RR 0.32, 95% CI 0.19–0.53, p < 0.001) compared to AADs in a recent meta-analysis [ 34 ]. Other than the effectiveness in reducing major endpoints, a reduced risk of incident dementia with AF CA was proposed by Saglietto et al in their systematic review and meta-analysis [ 35 ]. Moreover, it may also prevent the progression of paroxysmal to persistent AF [ 36 ].…”
Section: Atrial Fibrillation Catheter Ablationmentioning
confidence: 99%
“…Un reciente metaanálisis de cuatro estudios observacionales con un seguimiento medio de 4,5 años establece que la ablación mediante catéter en comparación con la no ablación confiere una protección significativa frente a la aparición de demencia, y el riesgo se reduce en algo más del 50% [ 40 ].…”
Section: Efectos Del Tratamiento De La Fibrilación Auricular En El De...unclassified